1972
DOI: 10.2118/3789-pa
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty of Oil in Place in Unconsolidated Sand Reservoirs - A Case History

Abstract: Reinterpretation of core analysis of an unconsolidated sand containing 8,000-cp oil indicates that the actual porosity of the sand in place is much lower than that arrived at even by special measurements on core samples recompacted under high confining pressure! The density log and sonic log from the same well support this conclusion. Introduction Accurate determination of oil in place in a reservoir is important when decisions are being made regarding develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…They also observed a strong dependency of residual oil saturation after waterflood (SORW) on S wi and proposed the following correlation between these two quantities. Elkins (1972) observed that the cores acquired from unconsolidated sands may result in overestimation of porosity and therefore the OOIP. They measured the porosity from cores to be 39% through conventional core analysis.…”
Section: Field Experiencesmentioning
confidence: 98%
“…They also observed a strong dependency of residual oil saturation after waterflood (SORW) on S wi and proposed the following correlation between these two quantities. Elkins (1972) observed that the cores acquired from unconsolidated sands may result in overestimation of porosity and therefore the OOIP. They measured the porosity from cores to be 39% through conventional core analysis.…”
Section: Field Experiencesmentioning
confidence: 98%
“…Elkins 18 observed that the cores acquired from unconsolidated sands may result in overestimation of porosity and therefore the OOIP. They measured the porosity from cores to be 39% through conventional core analysis.…”
Section: Techniques Used To Determine the Amount Of Remaining Oilmentioning
confidence: 99%
“…Both the overbalance pressure and the formation permeability are much greater than the suggested threshold levels (200 psia [1379 kPa] and 200 md), above which oil stripping could be significant.! Hence, it was suspected that even the heavy, 11 to 13 0 API [0.99-to 0.98-g/cm 3 ] crude could be flushed during coring. Therefore, to mitigate the core-flushing possibility, a low-fluid-Ioss drilling mud was used during coring of Well T03.…”
Section: Description Of Formations and Drilling Conditions For Well T03mentioning
confidence: 99%